الوعي الاجتماعي والحد من أخطار التلوث : دراسة ميدانية على الفئات المهنية - الضبع، عبدالرؤوف أحمد محمد (معهد التخطيط القومي, 2005)
This study discuses the issue of social awareness and its role in fighting the environmental pollution . This will be done through a theoretical analysis of the environmental pollution in its global then in its national dimension. On one part we will tackle air pollution, surface pollution, water pollution and food pollution . On the applicable side the study will discuss the relationship between social awareness and the dangers of pollution by comparing the level of social awareness in air pollution, water pollution etc. in four social categories. The study was applied on 400 persons from various occupational categories. The study is concerned with the following questions : 1- To what extent do the various four categories care about the pollution issue in comparison with other social issues ? 2- How do respondents in various social categories consider the problem of environmental pollution among other social problems? 3- What is the level of social awareness about air pollution in various social categories? 4- How do respondents think about the way to solve the pollution problem? The study concluded in the following : 1- There exists a big disparity among various professional chargers in identifying the importance of environmental pollution problem in comparison with other social problems . 2- The results of the study have revealed the increased level of social awareness among various social awareness about the negative effects of environment pollution problem . The awareness level was correlated with two important variables: education level and the profession . 3- The respondents offered many policy recommendations that aim to fight the pollution problem .
Keywords: الحضر -- البيئة -- الوعي الاجتماعي -- تلوث البيئة -- حماية البيئة -- النمو السكاني -- التخطيط العمراني -- التلوث الصناعي -- تلوث الهواء -- تلوث المياه -- الصرف الصحي -- المخلفات الصناعية